Antioxidant Activity Test Combination Inclusion of Curcumin-Î²-Cyclodextrin Complex and Aloe vera - T, Ardy Tanfil; Hermawati, Ema (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2022)
Free radicals occur from regular cellular metabolism. Free radicals are atoms or molecules with one or more unpaired electrons in their valence shell or outer orbit. Antioxidants are substances that are capable of neutralizing free radicals by contributing electrons to them. Curcumin is a polyphenolic molecule with numerous health benefits, including the capacity to combat free radicals as an antioxidant. Aloe vera is another plant known to contain a high concentration of bioactive compounds with antioxidant potential. Using the DPPH method, we evaluated the antioxidant capacity of the Curcumin-Î²-Cyclodextrin Complex and Aloe vera combination. According to the results of our investigation, the combination of curcumin-Î²-cyclodextrin and Aloe vera inclusion complexes has greater antioxidant capacity than the use of either component alone. However, additional research employing a variety of methodologies is required to determine the antioxidant potential of this combination.